2014
DOI: 10.1002/jhm.2212
|View full text |Cite
|
Sign up to set email alerts
|

Development of a discharge readiness report within the electronic health record—A discharge planning tool

Abstract: BACKGROUND: With increasingly complex pediatric inpatients, efficient and effective hospital discharge requires optimal interdisciplinary care coordination and communication. We describe the development of a discharge readiness report (DRR) for the electronic health record (EHR), an integrated summary of discharge-related information organized into a highly visible and easily accessible report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Although many transitions of care programs have supported implementation of specific care interventions at a hospital or health system level, there have been surprisingly few studies describing efforts to standardize the assessment of discharge barriers and prospectively engage individual patients . One emblematic study used stakeholder interviews and process mapping to develop a “readiness report” within their electronic medical record (EMR) . Aggregate data from the EMR including orders and discharge plans were coded, extracted, and summarized into a report.…”
Section: Discussionmentioning
confidence: 99%
“…Although many transitions of care programs have supported implementation of specific care interventions at a hospital or health system level, there have been surprisingly few studies describing efforts to standardize the assessment of discharge barriers and prospectively engage individual patients . One emblematic study used stakeholder interviews and process mapping to develop a “readiness report” within their electronic medical record (EMR) . Aggregate data from the EMR including orders and discharge plans were coded, extracted, and summarized into a report.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Far less attention has been paid to conceptually important constructs such as overall primary care experience, caregiver activation, and broad social determinants of health. These limitations in readmissions research might explain some of the counterintuitive findings observed thus far 7,14,15 and why tools that predict readmissions with high sensitivity and specificity are not yet available.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Current EHR products do not support this functionality. 41,42 However, a recent report highlights new solutions and has served as a model to avoid redundant documentation. 33 With respect to hospitalist-to-PCP handoff at discharge, previously identified essential discharge content (7 elements) aligned well with the content of continuous care documentation as well as meaningful use requirements, a universal incentive for hospitals.…”
Section: Figurementioning
confidence: 99%